Predisposing Factors for Erosive Tooth Wear in Permanent Teeth Among Asthmatic Children and Adolescents - Tomi Ujčič Samec; Janja Jan (Clinical and Experimental Dental Research, 2025)
ABSTRACT Objectives Epidemiological studies indicate that erosive tooth wear (ETW) is a common threat of tooth surface loss. The etiology of ETW is multifactorial. The prevalence of asthma is increasing in developed countries, especially in children. Studies evaluating ETW in asthmatic children are conflicting. With our study, we aimed to investigate the association between general and asthmatic factors and the presence of ETW. Methods Population of this cross‐sectional observational study consisted of children aged 6–17 years under treatment for asthma at University Medical Centre. ETW was determined using the Basic Erosive Wear Examination index. Questionnaires completed by parents and data from patients' medical records provided information on demographics, medical history, medication use, dietary habits, oral hygiene, fluoride exposure and type, dose, frequency, duration, and mode of asthma medication use. Results 379 asthmatic children participated in the study. The prevalence of ETW was 17.2% (n = 379). The mean total BEWE score was 0.76 ± 2.12. A statistically significant higher presence of ETW and higher total BEWE index were found in the group consuming acidic sports drinks (OR = 3.318), in the group aged 12–17 years (OR = 6.233), in the group using asthma medication for more than 3 years (OR = 3.379) and in the group using medication in the dry powder inhaled form (OR = 2.447). Conclusions Asthmatic children should avoid drinking acidic drinks since longer duration of asthma medication use is already associating them with higher ETW presence. From the ETW point of view, metered‐dose inhaled medications are more tooth‐friendly than dry powder inhaled forms.